The Effect of some Weather Factors on the Speed of the Sound Waves Inside the Surface Boundary Layer in Baghdad City - A. G. Mutar; N. A. Mohammed (Engineering and Technology Journal, 2017)
In this work the sound speed has been measured by a fast response anemometer in the surface boundary layer also the temperature and relative humidity has been measured to the same zoon then we tray to make a description to the relation between the sound speed and the other variables , the estimation of the average of Turbulent kinetic energy and the horizontal momentum flux was very important to have knowledge about the effect of turbulence advection variables on the sound speed , a practical equations Has proved to Describe the relation between the sound speed and the turbulence advection variables.